The Impact of Globalization on Political System And Governance in Indonesia - Lega, Michael (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The background of this research is related to two things, namely: how the impact of globalization on the political system and how the impact of globalization on governance in Indonesia. The purpose of this study is to analyze The impact of globalization on the political system and governance in Indonesia. Talking about the impact of globalization has given a big debate for globalization scholars, some say that globalization has too much negative impact and some argue that globalization has brought many positive impacts. This study uses a qualitative approach by analyzing data and literature sources related to The impact of globalization on the political system and governance in Indonesia. The study results show that the Positive impact of globalization on the political system in Indonesia is the increase in political participation, while the positive impact of globalization on the government system in Indonesia is the existence of an electronic government system (E-Government).